2020
DOI: 10.1097/acm.0000000000003868
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Interviews at Graduate Medical Education Training Programs: Determining Evidence-Based Best Practices

Abstract: The COVID-19 pandemic has had a profound impact on the nation's health care system, including on graduate medical education (GME) training programs. Traditionally, residency and fellowship training program applications involve in-person interviews conducted on-site, with only a minority of programs offering interviews remotely via a virtual platform. However, in light of the COVID-19 pandemic, it is anticipated that most interviews will be conducted virtually for the 2021 application cycle and possibly beyond.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 28 publications
0
73
0
Order By: Relevance
“…Interviews are an important component of the subspecialty fellowship application process, often affecting the final rank order of both programs and applicants [2,3]. Previously, most GME training programs conducted in-person interviews at the site(s) of the training program [4], A small number of programs previously reported their experiences with virtual interviews [4][5][6][7][8][9][10][11]. In these studies, applicants reported that they were able to present themselves to their satisfaction [10,11], gain a satisfactory understanding of the program [10], ask questions of fellows and faculty [11], and had an overall positive virtual interview experience [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Interviews are an important component of the subspecialty fellowship application process, often affecting the final rank order of both programs and applicants [2,3]. Previously, most GME training programs conducted in-person interviews at the site(s) of the training program [4], A small number of programs previously reported their experiences with virtual interviews [4][5][6][7][8][9][10][11]. In these studies, applicants reported that they were able to present themselves to their satisfaction [10,11], gain a satisfactory understanding of the program [10], ask questions of fellows and faculty [11], and had an overall positive virtual interview experience [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic brought about numerous challenges for interventional radiology (IR) residency programs in maintaining resident education, medical student recruitment and engagement of all learners ( 1 , 2 , 3 , 4 , 5 ). Travel bans and limitations on in-person gatherings necessary to mitigate viral spread resulted in significant disruptions to the traditional residency recruitment and interview process ( 6 , 7 , 8 , 9 , 10 , 11 ). A majority of IR residency programs adopted a virtual approach to the process in accordance with Association of Program Directors in Radiology Interventional Radiology guidelines as well as those of the Coalition for Physician Accountability ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Virtual interviews [3] can be high-yield, positive, and equitable for all applicants and medical schools. It is important to develop a detailed plan with adequate preparation for the interview process, including using standardized interview questions, recognize and respond to potential biases that may be amplified with the online interview format.…”
Section: Introductionmentioning
confidence: 99%